Empowerment Nurse as Leader Responsive Homecare Services to Diversity Culture at Nurul Hasanah Kutacane Hospital - Yusnaini Yusnaini; Dina Andriani Br Karo; Yessy Syahradesi; Nandara Priyanti Elna (Abdimas Paspama, 2024)
Culturally responsive nursing care has become a critical need in home care services, particularly in multicultural regions such as Aceh Tenggara District. Nurses are required not only to be clinically competent but also to lead nursing practices that are sensitive to patients' cultural backgrounds. This community service initiative aims to empower nurses at Nurul Hasanah Kutacane Hospital to become effective leaders in home care services that are adaptive to cultural diversity. The program included clinical leadership training, cultural competency workshops, and case-based mentoring. Evaluation results showed a significant improvement in nurses' knowledge and skills, with an average pre-test score of 55.8 and a post-test score of 84.4. The greatest improvement was observed in nurses' awareness of their role as leaders in homecare services, with an increase of 58.18%. In conclusion, this empowerment program contributed to enhancing nurses' capacity as humanistic and contextually responsive leaders in culturally sensitive homecare services.